If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8b + b = 0 Combine like terms: 8b + b = 9b 9b = 0 Solving 9b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '9'. b = 0 Simplifying b = 0
| 8x+13=35 | | 7h-4(n+5)=8h | | x^3-13x^2+40x=0 | | 6h-5+-2(24h-12)563= | | x^2-14=-20 | | 8y-6=14 | | n+n-17=13 | | 2k-7k=13 | | 6(x+2)+2x=44 | | -95e+6=4 | | -1+3x+6=4(x+3)-5 | | 4t-8=4(t+2) | | 2k-3k=13 | | 0.5f-2=0.16f | | 8n-11=6n+5 | | 6m+6=18 | | x^2+8x+30=3 | | 5(x+1)=5+12x | | 0.5f-2=0.16 | | 11x+6x-9=-19(1-x) | | 2((2x+1)-x)=3(3x-1) | | 8(y-2)=56 | | 4x-2-8x=3x | | 2(2x+1)-x=3(3x-1) | | 8n-9(n+1)=10 | | 12+6x-3x^2= | | 2x+17y+10x= | | 2(3-m)=-3-5m | | x^2+8x+20=3 | | x-23-(15-x)=4(x-8) | | 3r=9 | | 7(z+5)=50+42 |